Assistance in the Development of Personal Data Protection (PDP) Policies and Standard Operating Procedures (SOPs) for Digital Public Services - Didiek Trisatya; Sesilia Putri Maryanto; Adam Supriyadi; Raihan Eka Sanjaya (Jurnal Pengabdian IPTEK, 2026)
The rapid digitalization of public services at the village level has significantly increased the volume and sensitivity of personal data managed by local public institutions. Village administrations are required to ensure that personal data processing activities comply with legal, ethical, and security principles to prevent misuse, data breaches, and declining public trust. However, many village governments still lack formal internal policies and standardized procedures to operationalize personal data protection regulations within daily digital service activities. This condition highlights the need for practical and structured interventions that support local officials in translating regulatory requirements into implementable governance instruments. This study aims to examine the effectiveness of a structured assistance-based approach in supporting village officials to develop a Personal Data Protection (PDP) Policy and Standard Operating Procedures (SOPs) for Digital Public Services. A descriptive qualitative method was employed, with the study conducted at the Mintaragen Village Office, Indonesia. The assistance-based approach was implemented through four stages: initial assessment of digital service workflows and data management practices, capacity building on personal data protection principles, collaborative drafting of PDP policy and SOP documents, and evaluation of assistance outcomes. Data were collected through focused group discussions, semi-structured interviews, and document analysis, and were analyzed using descriptive qualitative techniques. The results show that the assistance-based approach improved village officials’ understanding of personal data protection responsibilities and enabled the successful formulation of a PDP Policy and Digital Public Service SOPs that are aligned with legal requirements and local operational needs. The findings indicate that participatory assistance can effectively bridge the gap between regulatory frameworks and practical implementation. This study contributes a replicable assistance-based model for strengthening personal data governance and enhancing the security, accountability, and professionalism of village-level digital public services.